Sri Lankan Teachers’ Online Classroom Management Abilities by School Type and Grade Section - Roshani Wickramanayake; H. M. Lalitha Kumari (International Journal on Integrated Education, 2022)
The purpose of this research was to study the potential of Sri Lankan teachers to manage their online classrooms. The study was focused to get an insight idea on how teachers manage time in their online classrooms, how teachers’ online classroom management ability varies by school type and how teachers’ online classroom management ability varies by grade section. Explanatory sequential mixed methodology was followed for the data triangulation. In the first phase of the study, quantitative data was collected by a survey questionnaire and analyzed before collecting the data in second phase. The second phase was followed based on the first phase results and the qualitative data was collected by semi-structured interviews and online classroom observations. The sample for the first phase was consisted of randomly selected 205 teachers in 10 selected 1AB and 1C schools and the second phase samples was purposively selected 10 teachers. Quantitative data was analyzed by descriptive statistical methods using tables, graphs and percentages while qualitative data was analyzed using thematic analysis. The study divulged that 66% of teachers managed time effectively in online classrooms while the teachers of 1AB schools are ahead of the teachers of 1C schools when managing the time in online classrooms. The study further revealed that the teachers of the Mathematics section showed the highest online classroom management skills comparatively to the other sections and teachers of the Commerce section showed the least online classroom management skills.